Stimulating Multilateral Treaty Making in the Teaching of International Law - Timothy L H McCormack; Gerry J Simpson (Legal Education Review)
Post-Pearce Report, many Australian law schools have moved to embrace the teaching of legal skills with an enthusiasm that few could have foreseen prior to 1987, or indeed, in the immediate aftermath of that Report. In many instances, it has been the fourthwave law schools which have been at the forefront of this development. The incorporation of skills into the undergraduate curriculum has always been a source of great concern and debate. The teaching of skills “on the run” as it were, is often seen to necessitate a corresponding lack of attention to the teaching of substantive law or theoretical perspectives and, as a result, true “integration of skills development, skills theory and practice, into a holistic and effective educative process has proceeded slowly”. A dismissive attitude to the old liberal education versus skills training debate has been adopted by those who now argue that the “existing challenge that confronts legal education … is the integration of doctrine, theory and practice into a unified, coherent curriculum”. Accepting this as the task presently facing legal educators, the underlying purpose of this paper is to demonstrate, by reference to an example of the use of moots in a Constitutional Law subject, that skills exercises can be used to good effect as part of course delivery to all students — not just those performing the skill at any particular time.